2012
DOI: 10.1016/j.neuroimage.2011.12.073
|View full text |Cite
|
Sign up to set email alerts
|

A reliable protocol for the manual segmentation of the human amygdala and its subregions using ultra-high resolution MRI

Abstract: The measurement of the volume of the human amygdala in vivo has received increasing attention over the past decade, but existing methods face several challenges. First, due to the amorphous appearance of the amygdala and the difficulties in interpreting its boundaries, it is common for protocols to omit sizable sections of the rostral and dorsal regions of the amygdala comprising parts of the basolateral complex (BL) and central nucleus (Ce), respectively. Second, segmentation of the amgydaloid complex into se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 76 publications
6
73
0
1
Order By: Relevance
“…In agreement with some previous studies (Entis et al, 2012;PrĂŠvost et al, 2011), we found that the Amunts et al (2005) AG map extends beyond the limits of the AG into the MTL white matter suggesting a mismatch between the anatomical location of the AG in our sample, and its location according to the Amunts et al (2005) atlas. Because of this limitation, and because source localization using probabilistic maps necessitates manipulation of MRI data into standard space, a process that can produce inaccuracies due to the deformations required (Yassa andStark, 2009), we used Mai (2008) atlas to manually segment the AG and its subnuclei groups in native space.…”
Section: Amygdala Segmentation and Subdivisionsupporting
confidence: 92%
“…In agreement with some previous studies (Entis et al, 2012;PrĂŠvost et al, 2011), we found that the Amunts et al (2005) AG map extends beyond the limits of the AG into the MTL white matter suggesting a mismatch between the anatomical location of the AG in our sample, and its location according to the Amunts et al (2005) atlas. Because of this limitation, and because source localization using probabilistic maps necessitates manipulation of MRI data into standard space, a process that can produce inaccuracies due to the deformations required (Yassa andStark, 2009), we used Mai (2008) atlas to manually segment the AG and its subnuclei groups in native space.…”
Section: Amygdala Segmentation and Subdivisionsupporting
confidence: 92%
“…Fourth, the inter-rater inconsistency in labeling is another factor potentially contributing unwanted variability, although our procedure of requiring the collaboration of two raters on each labeling dramatically reduced this type of variability. Moreover, as our reliability analysis noted, the reliability of our delineation had reached a good level, comparable to the reliabilities of some manually delineated anatomical regions, such as the amygdala and hippocampus (Entis et al, 2012;Geuze et al, 2005).…”
Section: Unwanted Sources Of Variabilitysupporting
confidence: 74%
“…No significant difference between inter-and intra-rater reliability was found (p b 0.05, Bonferroni correction). Remarkably, the reliability is comparable to the reported reliabilities of some manually labeled anatomical regions, such as the amygdala and hippocampus (Entis et al, 2012;Geuze et al, 2005), though the boundaries of the functional regions were not as clear as the boundaries of the anatomical regions. In summary, the raters had stable performance while delineating each FSR, and the delineations from different raters were highly consistent.…”
Section: Reliability Of the Delineation Of Fsrssupporting
confidence: 60%
“…Only very recently have refinements in the acquisition and analysis of fMRI data allowed subregion function to be segregated effectively during emotional tasks such as avoidance learning [45] and facial expression recognition [21,46]. Similarly, effective structural identification of human amygdalar subregions and assessment of their functional connectivity using imaging techniques is still fairly new [for example, see [47][48][49][50][51]. Therefore, most of our understanding of causal neurochemical pathways in amygdalar circuitry related to fear and anxiety has derived from extensive studies using rodent and non-human primate models [for example, see 9,52-58].…”
Section: Amygdala Reactivity In Anxiety Disordersmentioning
confidence: 99%